EXPERIMENTAL STUDY AND SIMULATION OF ATTRACTIVE FORCE FORMULATION OF DIMENSIONAL FLOATING SPHERES - Erlina
Objects that float on the surface of the water for a certain period of time will spontaneously interact and move with each other to form colonies. This interaction is caused by the attractive force between two objects that interact. This deformation is caused by the nature of liquid which has capillary interaction when it comes in contact with other particles. This results in the occurrence of meniscus in the boundary plane between the two. This phenomenon has been previously investigated using millimeter-sized objects and spherical to facilitate analytical calculations and the results obtained that two particles at a certain distance, within a certain period of time will come closer to each other and after they have contact, both tend to bind and difficult to escape if given a disturbance. This final project aims to observe this phenomenon with macro-sized objects (centimeter scale) and compare them with previous research. The focus of this research is to formulate the amount of attractive force between two particles that interact on the surface of the water.